A utilização das ferramentas da qualidade para a resolução de não conformidades em uma empresa de embalagens plásticas no interior do Rio Grande do Sul - Borille, Leonardo Scorsatto (2021)
Companies continually seek to improve the process, as they are facing a scenario that requires cost reduction and quality assurance. In this way, the work aims to apply quality tools in the production process of plastic packaging, seeking to minimize nonconformities. The application of quality tools were carried out in the two sectors with the highest occurrence of nonconformities. For this, the sectors were identified and also the three problems with the highest incidence in each of the sectors. The following tools were used: Check Sheet, Pareto Diagram, Flowchart, Brainstorming, Ishikawa Diagram and 5W2H. They made it possible to understand the process and identify the root cause of each problem, enabling the execution of an action plan, as well as the reduction of non-conformities, the improvement of internal indexes and the reduction of costs.